Characteristics of quality activities in a tertiary teaching hospital in Western Australia. (2nd July 2021) - Li, Qun Catherine; Karnon, Jonathan; Towler, Simon; Codde, Jim
Abstract: Background: Despite all the resourcefulness and efforts in the last 30 years for quality in healthcare, safety and quality considerations are recognized with up to 17% of total hospital activity and expenditure related to adverse events. A knowledge gap is identified in the literature that few studies have reported from a whole hospital perspective on what and how quality activities are being performed, particularly in the Australian context. Objective: This study aims to describe the characteristics of quality activities in a tertiary quaternary hospital in Western Australia. Methods: Data from the study hospital's electronic quality management system Governance, Evidence, Knowledge and Outcome between 1 January 2015 and 31 December 2019 was analysed by using descriptive and thematic methods. Results: Quality assurance (QA) accounted for 68.3% of all quality activities in the study hospital. Principal investigators of activities were mostly in clinical roles and relatively senior in their profession. Collaboration within the same profession and same team was common, but much less so across departments. The median quality cycle length measured by proposal submission to completion was 202 days, but 190 days when measured by proposal approval to completion. A majority (93.2%) of quality activities were undertaken as part of everyday business. Common issues outlined in activity reports were documentation and compliance 44.8% ( n  = 100), data and tool limitations 10.8% ( n  = 24), variation in care 9.9% ( n  = 22), process 9.4% ( n  = 21), and knowledge and awareness 9.0% ( n  = 20). Common recommendations to address the issues were communicating findings to relevant teams and governance committees 26.8% ( n  = 104), further data collection including re-audit 26.0% ( n  = 101), education and training 20.4% ( n  = 79), process review and/or development 13.9% ( n  = 54), and policy/guidelines review and/or development 4.4% ( n  = 17). Conclusion: Understanding the characteristics of quality activities from a whole hospital perspective provides insights and informs discussions relating to the efficiency and effectiveness of quality activities in hospitals. Embedding quality activities into everyday business is achievable for hospitals but considerations need to occur on how to sustain staff motivation and enthusiasm by helping individuals and teams reach the ultimate goals for improvement and keeping performance monitoring as close to the real time of care as possible. There is a need to transform QA into quality improvement, with the 90-day cycle being a feasible target for QA in hospitals.